Contextual Factors That Affect Pedagogical Accompaniment And Teacher Performance In Rural Contexts - Muñoz Pilozo, Adriana Georgina (2025)
Abstract: The present study analysed the incidence of pedagogical accompaniment on the academic performance of rural teachers in the canton of Milagro, Ecuador. Objective: To identify how contextual factors influence the effectiveness of accompaniment, considering variables such as planning, execution and evaluation of learning. Methodology: The research used a quantitative, correlational and cross-sectional approach. A structured survey was administered to 144 teachers in rural institutions, with a validated instrument and a high reliability index (α = 0.87). Spearman correlation analysis, ANOVA and cross-tabulation were used. Results: The results revealed a positive and significant correlation between pedagogical support and teacher performance (Rho = 0.229; p = 0.006), especially in the dimensions of planning (57.6%), implementation (58.3%) and evaluation (56.9%). However, the model explained only 2.5% of the variability, suggesting the influence of other factors such as continuing education, institutional support and peer collaboration. Discussion: The discussion contrasted these findings with international studies, highlighting that mentoring is most effective when contextualised and linked to sustainable education policies. The literature supports that self-efficacy, teacher motivation and technology integration are key determinants in rural contexts. Conclusion: It was concluded that pedagogical accompaniment is a relevant tool for improving teacher performance, but its impact depends on structural conditions, adequate resources and collaborative practices. Promoting a comprehensive approach adapted to the rural environment is essential to ensure its effectiveness.